2023
DOI: 10.1186/s12960-023-00864-y
|View full text |Cite|
|
Sign up to set email alerts
|

Systems that evaluate international equivalency in health-related professions: a scoping review with a focus on Canada

Mark Lafave,
Yasaman Amannejad,
Ulkar Mammadova
et al.

Abstract: Health workforce planning has become a significant global problem considering there are estimates of an 18 million healthcare provider shortfall by 2030. There are two mechanisms to address healthcare worker shortages: (1) domestic education of those professions and (2) integration of internationally educated health professionals. Integration of internationally educated health professionals into the Canadian healthcare system requires: (1) reductions in systemic and administrative barriers and (2) development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Yasaman Amannejad.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Yasaman Amannejad.…”
mentioning
confidence: 99%